2021
DOI: 10.1002/cbin.11606
|View full text |Cite
|
Sign up to set email alerts
|

The frequency window effect of sinusoidal electromagnetic fields in promoting osteogenic differentiation and bone formation involves extension of osteoblastic primary cilia and activation of protein kinase A

Abstract: Electromagnetic fields (EMFs) have emerged as a versatile means for osteoporosis treatment and prevention. However, its optimal application parameters are still elusive.Here, we optimized the frequency parameter first by cell culture screening and then by animal experiment validation. Osteoblasts isolated from newborn rats (ROBs) were exposed 90 min/day to 1.8 mT SEMFs at different frequencies (ranging from 10 to 100 Hz, interval of 10 Hz). SEMFs of 1.8 mT inhibited ROB proliferation at 30, 40, 50, 60 Hz, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
(144 reference statements)
1
7
0
Order By: Relevance
“…Similar effects have been observed for mesenchymal stem cells exposed in vitro to an alternating electric current of 5-40 μA at a frequency between 5 and 10 Hz (EF) [10,42,55]. Zhou described a PKA-driven optimal effect of electromagnetic fields with 50 Hz and 1.8 mT on osteogenic differentiation and mineralization in an animal model [60]. Considering the outcomes of previous studies, in the present study, we investigated the potential effect of combined specified electric and magnetic field (EFMF) exposure on primary human osteoblasts to modify cellular and molecular biological pathways in vitro and the parameters that may support and stimulate the biological processes of bone fracture healing in vivo.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar effects have been observed for mesenchymal stem cells exposed in vitro to an alternating electric current of 5-40 μA at a frequency between 5 and 10 Hz (EF) [10,42,55]. Zhou described a PKA-driven optimal effect of electromagnetic fields with 50 Hz and 1.8 mT on osteogenic differentiation and mineralization in an animal model [60]. Considering the outcomes of previous studies, in the present study, we investigated the potential effect of combined specified electric and magnetic field (EFMF) exposure on primary human osteoblasts to modify cellular and molecular biological pathways in vitro and the parameters that may support and stimulate the biological processes of bone fracture healing in vivo.…”
Section: Introductionsupporting
confidence: 54%
“…These previously described cellular mechanisms and principles of the potential mode of action of electromagnetic field exposure are supported by a recent study by Zhou 2021, who applied inductively coupled electromagnetic fields (IC) in a rat osteoblast system. These authors showed, also that exposure to sinusoidal electromagnetic fields promotes osteogenic differentiation and bone formation through activation of protein kinase A [60]. In this context it is important to mention, that Rodemann applied inductively coupled electromagnetic fields (IC), which are an integrative part of the combination of alternating magnetic and electric fields (CS), we used in our experiments and were also used by Darwiche [12] in a sucessful animal study.…”
Section: Discussionmentioning
confidence: 99%
“…myocardial fibrosis and oxidative stress in the heart of hypertensive rats (He et al, 2021). ASP could antagonize 5-FU-induced oxidative stress injury to suppress apoptosis in the liver.…”
Section: Discussionmentioning
confidence: 93%
“…Cells treated with ASP were subjected to calcium deposition detection by ARS. @, P < 0.05; @@, P < 0.01; @@@, P < 0.001. more and more attention due to the ease of availability, less immune rejection, and avoidance of ethics (Zhou et al, 2021). Therefore, hDPSCs are suitable sources of tissue repair not only in dentine generation but also in regeneration-related diseases, such as diseases related to dental pulp (Liu et al, 2020;Zhou et al, 2019).…”
Section: Figure 1 Asp Enhances Hdpscs Proliferation (A)mentioning
confidence: 99%
See 1 more Smart Citation